2017
DOI: 10.1021/acschemneuro.7b00189
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometric Imaging of Ceramide Biomarkers Tracks Therapeutic Response in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a serious public health problem and the leading cause of death in children and young adults. It also contributes to a substantial number of cases of permanent disability. As lipids make up over 50% of the brain mass and play a key role in both membrane structure and cell signaling, their profile is of particular interest. In this study, we show that advanced mass spectrometry imaging (MSI) has sufficient technical accuracy and reproducibility to demonstrate the anatomical distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
(69 reference statements)
3
25
0
Order By: Relevance
“…Mitochondrial dysfunction is a fundamental pathogenic event in most neurodegenerative diseases. Findings from rat models of TBI have revealed that ceramide is the first lipid to accumulate in the mitochondria after TBI (Roux et al, 2016), suggesting it may serve as a therapeutic indicator (Barbacci et al, 2017). Ceramide accumulation causes mitochondrial dysfunction (Novgorodov et al, 2016), which is associated with increased mitochondrial fission and excessive ROS production (Zhao et al, 2018).…”
Section: Sirtuins Improve Mitochondrial Function and Reduce Oxidativementioning
confidence: 99%
“…Mitochondrial dysfunction is a fundamental pathogenic event in most neurodegenerative diseases. Findings from rat models of TBI have revealed that ceramide is the first lipid to accumulate in the mitochondria after TBI (Roux et al, 2016), suggesting it may serve as a therapeutic indicator (Barbacci et al, 2017). Ceramide accumulation causes mitochondrial dysfunction (Novgorodov et al, 2016), which is associated with increased mitochondrial fission and excessive ROS production (Zhao et al, 2018).…”
Section: Sirtuins Improve Mitochondrial Function and Reduce Oxidativementioning
confidence: 99%
“…Neurodegeneration is associated with alteration of sphingolipid metabolism and composition. In acute injuries such as stroke, concussion, spinal cord injury (SCI), or traumatic brain injury (TBI), activation of SMases and glycosidases and upregulation of ceramide and glycolipid levels are among the first responses of the injured tissue (Abe et al, 2018; Barbacci et al, 2017; Brunkhorst et al, 2015; Gu et al, 2013; Horres and Hannun, 2012; Jones and Ren, 2016; Kubota et al, 1989; Novgorodov and Gudz, 2011; Ong et al, 2015; Roux et al, 2016; Sajja et al, 2018). C18:0 and C18:1 ceramide, typical neuronal ceramides synthesized by CerS1, are dysregulated within 24 h after the insult and can be used as biomarkers for TBI (Sajja et al, 2018).…”
Section: Sphingolipid Levels In Nervous System Injuries and Neurodegementioning
confidence: 99%
“…This hypothesis is supported by our data on sphingolipid alterations after injury. Previous lipidomics studies in TBI have reported reductions in SM and increases in ceramides [13,66], speaking to elevated SMase activity. Indeed, multiple activators of SMase activity (such as tumor necrosis factor alpha [67], arachidonic acid [68] and glutamate [69]) are established components of TBI pathology.…”
Section: Discussionmentioning
confidence: 99%